1994
DOI: 10.1002/bdm.3960070405
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prior expectations and outcome knowledge on polygraph examiners' decisions

Abstract: The present study deals with the question of whether judgments made by experts working in familiar contexts are affected by prior expectations and beliefs. Two experiments in which prior expectations were manipulated were designed to determine whether and to what extent polygraph examiners are affected by their prior expectations when analyzing and interpreting polygraph charts. Prior expectations affected the examiners' judgments when the polygraph charts did not include clear indications of guilt or innocenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
4
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 22 publications
5
71
4
1
Order By: Relevance
“…In one study, Elaad, Ginton, and Ben-Shakhar (1994) asked polygraph examiners from the Israeli Police Force to evaluate and interpret charts previously deemed inconclusive. Some examiners, but not others, were told that the suspect had ultimately confessed.…”
Section: Confessions Corrupt Other Evidencementioning
confidence: 99%
“…In one study, Elaad, Ginton, and Ben-Shakhar (1994) asked polygraph examiners from the Israeli Police Force to evaluate and interpret charts previously deemed inconclusive. Some examiners, but not others, were told that the suspect had ultimately confessed.…”
Section: Confessions Corrupt Other Evidencementioning
confidence: 99%
“…But what do such field studies look like? Research has shown that prior information about the guilt of a suspect-for example, about a confession-influences the outcomes of subsequent forensic tests, including the outcomes of lie detection tests (e.g., Bogaard, Meijer, Vrij, Broers, & Merckelbach, 2014;Elaad, Ginton, & Ben-Shakhar, 1994;Kassin, Dror, & Kukucka, 2013). Given the large number of degrees of freedom, especially when it comes to interpreting fMRI data, analysis of deception detection results may be prone to biasing observer effects.…”
Section: Legal Implicationsmentioning
confidence: 99%
“…The present study, both in its conception and in its results, extends an earlier paper by Elaad, Ginton and Ben-Shakhar (1994). In that study, expert polygraph examiners were given inconclusive polygraph charts for interpretation and scoring.…”
Section: Discussionmentioning
confidence: 88%